KEPEKAAN PERTUMBUHAN ANAKAN BALANGERAN (Shorea balangeran) (Korth) TERHADAP TINGGI GENANGAN - Muhammad Khalil; Sulaiman Bakri; Basir Basir (Universitas Lambung Mangkurat, 2020)
This study aims to determine the growth response of seedlings to the height of inundation measured from the root neck that has been marked with a sewing thread with a distance of 1 cm. tillering diameter to the measured inundation height from the root neck sewing thread with a distance of 1 cm and knowing the percentage of life of the seedlings of Shorea balangeran obtained by calculating the number of live tillers divided by the number of dead tillers multiplied by 100%. The benefits of research so that it can be an information material and material for consideration for the relevant agencies to determine the location of planting of prince baloons related to the height of the puddle in a place. The research was carried out using a completely randomized design (CRD) and diversity analysis method. The results showed that the highest increase in the number of prince puppies occurred on the PSP treatment (Immersion to Polybag) with an increase in the average value of 2.09 cm while the lowest increase in the height of the prince's tillers occurred with the PSUB treatment. average 1.16 cm. The largest increase in diameter of prince puppies occurred in TP treatment (without immersion) with an average increase in diameter of 0.17 mm while the lowest increase in diameter of bald puppies occurred in the treatment of PSUB (Immersion to End of Stem) with an average increase in diameter of 0.052 mm. The percentage of life of all tillers Shorea balangeran is 78.75% (63 live tillers from 80 children studied).Keywords: Peat Swamp, Accretion, Inundation, Shorea balangeran (Korth.) Addition Burck